(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2022)
Purpose: The aim of this paper is to provide an overview and analysis of literature dealing with the possibilities for applying augmented reality (AR) in marketing and the impact of AR on marketing in the era of digital transformation of business. Though attractive, this topic is still insufficiently explored. Methodology: The paper uses a bibliometric method - citation and co-citation analysis in the Web of Science and Scopus citation databases. Data analysis was performed using the VOSviewer software tool for information construction, analysis and visualization. Results: The conducted research revealed that there is an increasing trend in the number of research papers dealing with the AR and marketing topics. The specific topics dealt with in the papers are primarily related to the impact of AR on business, creating customer loyalty, sales increase and other marketing activities. Conclusion: AR is a powerful and influential tool the use of which improves communication with customers and, at the same time, sales strategies and processes. AR is based on immersing customers into a new experience, by showing virtual objects in the users’ real-world environment and creating harmony between the digital and the real-world environment so that the boundaries between them disappear. It is manifested as a form of experiential marketing, since it focuses both on a product and a service, and on the entire experience created for customers.